Faktor Yang Berhubungan Dengan Kejadian Premenstrual Syndrome (PMS) Pada Remaja Putri Di SMAN 6 Bone - Jumriani Arianti; Muhammad Ikhtiar; Masriadi; Muhammad Khidri Alwi; Nurul Ulfah Mutthalib (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Premenstrual syndrome is a collection of physical and psychological symptoms and behavioral changes that occur before or during menstruation. The prevalence of premenstrual syndrome in Indonesia is increasing, and around 80% of adolescent women experience premenstrual syndrome symptoms that can interfere with daily life. PMS symptoms can cause absenteeism, decreased academic achievement, and non-participation in physical activities, as well as causing significant social stress among female students. This type of research is quantitative with a cross-sectional approach. The population in this study were female adolescents at SMAN 6 Bone. The sampling technique used the stratified random sampling method with a sample size of 196 female students. The data analysis method used univariate, bivariate, and multivariate analysis. From the results of the study, it was found that there was a relationship between vitamin D intake and the incidence of premenstrual syndrome, namely p value = 0.013, there was a relationship between physical activity and the incidence of premenstrual syndrome, namely p value = 0.000, there was a relationship between sleep quality and the incidence of premenstrual syndrome, namely p value = 0.003. At the same time, family history had no relationship with the incidence of premenstrual syndrome, namely p value = 0.240. The variable with the greatest or dominant relationship with the incidence of premenstrual syndrome was physical activity, with a standardized coefficient Beta result of 0.267, which was more significant than other variables.